2011
DOI: 10.2298/jmmb110331011p
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure characterization of porous microalloyed aluminium-silicate ceramics

Abstract: Kaolinite and bentonite clay powders mixed with active additives, based on Mg(NO3)2 and Al(NO3)2, sintered at high temperatures produce very porous ceramics with microcrystalline and amorphous regions and highly developed metalized surfaces (mainly with magnesium surplus). Microstructure investigations have revealed non-uniform and highly porous structure with broad distribution of grain size, specifically shaped grains and high degree of agglomeration. The ceramics samples were characterized by scanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Figure S6 showed the FTIR spectra of the SAM and CsPbBr 3 QDs‐SAM with different annealing temperature. A broad band from 992 cm −1 to 1155 cm −1 corresponding to amorphous aluminum silicate (often expressed as x Al 2 O 3 ⋅ y SiO 2 ), was presented in both CsPbBr 3 QDs‐SAM and SAM. Particularly, this broad band became stronger with increasing the annealing temperature.…”
Section: Figurementioning
confidence: 99%
“…Figure S6 showed the FTIR spectra of the SAM and CsPbBr 3 QDs‐SAM with different annealing temperature. A broad band from 992 cm −1 to 1155 cm −1 corresponding to amorphous aluminum silicate (often expressed as x Al 2 O 3 ⋅ y SiO 2 ), was presented in both CsPbBr 3 QDs‐SAM and SAM. Particularly, this broad band became stronger with increasing the annealing temperature.…”
Section: Figurementioning
confidence: 99%
“…If the anneal temperature was increased to 100 8 8C, the PL intensity of CsPbBr 3 QDs-SAM decreased to 70 %o ft he initial intensity.W hen we did the same thermal anneal treatments for the bare CsPbBr 3 QDs at 50 8 8Ca nd 100 8 8C, which just could keep 60 %a nd 20 %o ft he initial intensity,r espectively.T hese results indicated that the CsPbBr 3 QDs-SAM powder sample exhibited much better thermal stability than the CsPbBr 3 QDs. Figure S6 showed the FTIR spectra of the SAM and CsPbBr 3 QDs-SAM with different annealing temperature.Abroad band from 992 cm À1 to 1155 cm À1 corresponding to amorphous aluminum silicate (often expressed as x Al 2 O 3 ·y SiO 2 ), [22] was presented in both CsPbBr 3 QDs-SAM and SAM. Particularly,t his broad band became stronger with increasing the annealing temperature.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[21] Thes ame principle can also be employed to strengthen the photostability of CsPbBr 3 QDs-SAM. Figure S6 showed the FTIR spectra of the SAM and CsPbBr 3 QDs-SAM with different annealing temperature.Abroad band from 992 cm À1 to 1155 cm À1 corresponding to amorphous aluminum silicate (often expressed as x Al 2 O 3 ·y SiO 2 ), [22] was presented in both CsPbBr 3 QDs-SAM and SAM. It was observed that the PL intensity of CsPbBr 3 QDs-SAM underwent ignorable change at 50 8 8C ( Figure S5).…”
mentioning
confidence: 99%
“…Figure A shows the FTIR spectra of the SAM and CdSe/CdS/ZnS QD–SAM phosphor with varied QD wt %. A broad band from 992 to 1155 cm –1 corresponding to amorphous aluminum silicate ( x Al 2 O 3 · y SiO 2 ) was presented in both the CdSe/CdS/ZnS QD–SAM phosphor and SAM, which may be a proof of existence of Al 2 O 3 and SiO 2 in the CdSe/CdS/ZnS QD–SAM. Particularly, this broad band became stronger with increasing DBATES content.…”
mentioning
confidence: 89%